Analysis of Start-Up Share Valuation on the Indonesia Stock Exchange for the 2017-2022 Period Using the DFC GMV and Tobins'q Methods - Hartono Hartono (Journal La Bisecoman, 2022)
The phenomenon of the proliferation of startup companies in Indonesia that cannot be separated from the use of digital technology brings a fragrant aroma to venture capital investment companies. The number of startup companies that received the investment funds are bringing them to the Indonesian Stock Exchange by conducting an IPO even though the company has not been established for a long time. There is a correlation between the rapid growth of startups in Indonesia with "bubble.com" the phenomenon that occurred in Silicon Valley between the years 1999 and 2000. The surge in assets of startup companies is currently caused by stock valuation, which is based on a single valuation, without assessing assets, cash flows, or other aspects that affect the valuation value of a company. Recently, the stock price of startup companies began to fall, and is considered the same as the phenomenon "bubble.com" another indication is that there are mass layoffs of company employees; this condition also occurs in Silicon Valley. In this case, it is necessary to conduct an intrinsic assessment of startup shares empirically and in accordance with applicable valuation standards to see the condition of the company as a whole. The valuation methods used in this study are Gross Merchandise Value, Discounted Cash Flow and Tobins'q, it is expected that these three methods can represent the valuation analysis of the company so that investors know the intrinsic value of startup companies and are expected not to be Overvalued.